THE ASSESSMENT OF STRENGTH PROPERTIES OF HISTORICAL MORTARS FOR SUSTAINABLE RENOVATIONS - Pokorny, Jaroslav; t, Jan; Scheinherrová, Lenka; Navara, Tomás; Javorsky, David (International Multidisciplinary Scientific GeoConference SGEM, 2024)
Old buildings, in particular, those coming from the first half of 20" century often suffer With increased dampness in masonry coming from different sources. Some of them, however, have aesthetically rendered valued facades which are worth saving. For the design of new alternative mortars for renovation interventions, it is essential to obtain properties of original renders. Mechanical properties of mortars are in general assessed on standardized test samples; however, this approach cannot be always well applicable for in situ taken mortars or rendering materials. This paper is devoted to the specification of complex experimental procedure allowing to effectively obtain strength parameters of in situ collected renders which will be comparable with laboratory produced alternative mortars. Throughout this paper the detailed description of in situ collected renders sampling procedure is provided. Further, the adjusted approach of flexural strength testing in three-point arrangement and compressive strength tests for both cut renders samples and laboratory prepared alternative mortars is outlined. The suitable set up of testing procedures of materials coming from old or historical buildings introduces a key area for obtaining experimental relevant data being the bases for their sustainable renovations.